2018
DOI: 10.1007/s11013-018-9593-8
|View full text |Cite
|
Sign up to set email alerts
|

Magic Moments: Determinants of Stress Relief and Subjective Wellbeing from Visiting a Cultural Heritage Site

Abstract: We provide an experimental evaluation of the impact of aesthetic experiences in terms of stress reduction (cortisol levels) and wellbeing increase. The test experience is a visit to the vault of the Sanctuary of Vicoforte, Italy. Data have been collected using a double step method. A structured interview in relation to the individual subjective well-being has been administered to a sample of 100 subjects. In addition, a sample of their saliva has been taken, and its cortisol level measured, before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 53 publications
3
51
0
3
Order By: Relevance
“…In this study, wellbeing has been assessed through measures of depression, stress, anxiety, resilience, peace of mind and the strategies employed to regulate the emotional upheavals. This approach has been reported in earlier studies that have examined wellbeing in terms of anxiety, stress, and depression [11][12][13], emotion regulation [14]and as a measure of peace of mind [15]. Wellbeing has also been shown to positively correlate with resilience [16] Previous research has suggested that yoga can be used as a non-pharmaceutical measure or as a complement to drug therapy for treatment or cure of modern epidemic diseases like mental stress, obesity, diabetes, hypertension, coronary heart disease, and chronic obstructive pulmonary disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, wellbeing has been assessed through measures of depression, stress, anxiety, resilience, peace of mind and the strategies employed to regulate the emotional upheavals. This approach has been reported in earlier studies that have examined wellbeing in terms of anxiety, stress, and depression [11][12][13], emotion regulation [14]and as a measure of peace of mind [15]. Wellbeing has also been shown to positively correlate with resilience [16] Previous research has suggested that yoga can be used as a non-pharmaceutical measure or as a complement to drug therapy for treatment or cure of modern epidemic diseases like mental stress, obesity, diabetes, hypertension, coronary heart disease, and chronic obstructive pulmonary disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing research on the benefits of receptive cultural engagement for mental health ( Fancourt and Finn, 2019 ). Attendance at cultural events, such as theatres, art galleries or museums, and cultural heritage sites has been found to (i) improve wellbeing and life satisfaction ( Cuypers et al, 2012 ; Grossi et al, 2018 ; Meeks et al, 2017 ; Renton et al, 2012 ), (ii) reduce the risk of developing depression, and (iii) reduce anxiety and depression ( Clements-Cortès, 2012 ; Fancourt and Tymoszuk, 2018 ). Still, not all people can access these cultural events, and, therefore, their potential benefits equally.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, links are being made between various aspects of heritage and its relationship to well-being. In addition to notable books that touch upon these links such as Museums, Health and Well-Being [1], Human Well-Being and the Natural Environment [2] and Heritage and Community Engagement [3], recent articles have appeared in a broad array of disciplinary journals on issues including the impact of archaeological excavations on happiness [4], the therapeutic effects of community-based heritage conservation [5], and how the aesthetic experience of heritage sites can reduce stress [6]. While well-being is rarely indexed in major heritage handbooks or readers [7][8][9][10], there is a growing body of literature indicating that cultural heritage, including rock art [11], ancient architecture [12], written heritage [13], material culture [14] and intangible cultural practices [15], is very important for contemporary well-being for diverse groups of people.…”
Section: Links Between Heritage and Well-beingmentioning
confidence: 99%